Investigation of HPLF-111624 in Modified Experimental Models of Ulcerative Proctitis and Anal Fissure in Rats - Onkaramurthy M; Azeemuddin MM; Baig MR; Kendagann PH; Rafiq M; Babu UV (Dove Medical Press, 2022)
Mallappa Onkaramurthy,1 Mohammed Mukhram Azeemuddin,1 Mirza Rizwan Baig,2 Pavan Heggadadevanakote Kendaganna,2 Mohamed Rafiq,1 Uddagiri Venkanna Babu3 1Discovery Sciences Group, Research and Development Center, Himalaya Wellness Company, Bengaluru, Karnataka, India; 2Microbiology and Toxicology Department, Research and Development Center, Himalaya Wellness Company, Bengaluru, Karnataka, India; 3Research and Development Center, Himalaya Wellness Company, Bengaluru, Karnataka, IndiaCorrespondence: Mohamed Rafiq, Email dr.rafiq@himalayawellness.comBackground: Although ulcerative proctitis (UP) and anal fissure (AF) are common anorectal diseases, there are no appropriate experimental models to screen the drugs intended for these conditions. In this context, existing experimental models mimicking these diseases were modified and the polyherbal formulation, HPLF-111624 was evaluated in these models.Objective: To establish animal model for UP and AF and to evaluate polyherbal formulation, HPLF-111624 in these disease models.Methods: An experimental model of UP was selected based on the modification of the ulcerative colitis model using different concentrations of acetic acid. The concentration used for induction were 2.5%, 5% and 10% v/v and different weights used to induce AF were 25 g, 50 g and 100 g, which were selected based on the severity of inflammation, fecal score, gross pathology, and histopathological evaluation. Furthermore, these animal models were used to evaluate the efficacy of HPLF-111624, a polyherbal formulation known to be beneficial in anal diseases.Results: Acetic acid at 5% produced typical pathological changes that resembled UP, with a significant increase in the fecal score, gross lesion, and histopathological changes. Similarly, among the three weights, physical injury with a 100 g weight produced significant changes in the histopathological score in the model of AF. Intervention with HPLF-111624 at doses of 250 and 500 mg/kg b.wt., showed a reduction in the inflammatory cytokines and a significant improvement in the histopathological findings in both the conditions.Conclusion: The results showed that the modified experimental models for UP and AF resemble the human pathological conditions and are simple, versatile and may be used for screening drugs intended for these conditions. Intervention with HPLF-111624 was found to be effective in improving the pathological state of UP and AF.Graphical Abstract: Keywords: anorectal disorders, ulcerative proctitis, anal fissure, inflammation, histopathological evaluation, polyherbal formulation